Avaliação mediadora na educação infantil: acompanhamento do processo de desenvolvimento da criança - Uchôa, Solange de Cássia do Nascimento (2023)
The object of study of this dissertation is the Mediating Assessment in Early Childhood Education with multi-age groups in an Early Childhood Education Unit in the municipal network of São Paulo. Based on this object of study, some concerns emerged that motivated and directed the development of this research: Does the evaluation process of four and five year old children include monitoring their development process? Are the instruments used adequate to monitor their real development in the context of multi-age groups? With the questions presented, the general objective was to investigate how the process of evaluating children occurs in the selected Early Childhood Education Unit. The specific objectives of the research include: analyzing how the teacher evaluates the child's development in the daily life of Early Childhood Education; identify which instruments are used by the teacher to assess the child’s development. It is assumed that assessment in Early Childhood Education should not aim to judge, but rather to monitor the child's knowledge and skills, to then plan future pedagogical practices that redefine attitudes and reorganize the learning environment. It is assumed that some teachers, even having access to official guiding documents, may have difficulty understanding how the evaluation process in Early Childhood Education takes place, using tools and strategies for preparing standardized descriptive reports, which do not always reveal the child's real development. Based on the objectives presented, we developed a qualitative research. The instruments adopted were: observation, semi-structured interview, analysis of the school's Political-Pedagogical Project. We defined as the research universe an Early Childhood Education unit with a multi-age group in the city of São Paulo. The research participants will be two Early Childhood Education teachers, from a multi-age group (four and five years old) and the unit coordinator. The research is based on the following authors: Jussara Hoffmann, João and Julia Oliveira-Formosinho, Paulo Fochi; in official documents and specific legislation that deals with assessment in Early Childhood Education. After content analysis, two categories emerged, with two indicators in each category: 1) Assessment Practices in Early Childhood Education (Indicators: Assessment Design; Assessment instruments); 2) In-context training on Assessment in Early Childhood Education (Indicators: Knowledge of Assessment Guidelines for Early Childhood Education; Access to training on the topic of Assessment). The results indicate that the participants know the concept of the mediating assessment theme in Early Childhood Education, evaluating with the aim of monitoring the child's development, respecting their individuality, however, they take the children's age into consideration, which defends the development theory. However, it is important to highlight that the organization by multi-age grouping is based on social historical theory. It is worth mentioning that the teachers had no training on the topic of evaluation in the multi-age group. The results also indicate that the participants use different evaluation instruments (Letter of Intent, Logbook, photographs, videos, notes and Learning Monitoring Report), prioritizing some in their practice, with difficulty in others.